Optimization-based humanoid robot navigation using monocular camera within indoor environment - Han, Young Joong; Kim, In Seok; Hong, Young Dae (ETRI Journal, 2018)
Robot navigation allows robot mobility. Therefore, mobility is an area of robotics that has been actively investigated since robots were first developed. In recent years, interest in personal service robots for homes and public facilities has increased. As a result, robot navigation within the home environment, which is an indoor environment, is being actively investigated. However, the problem with conventional navigation algorithms is that they require a large computation time for their building mapping and path planning processes. This problem makes it difficult to cope with an environment that changes in real-time. Therefore, we propose a humanoid robot navigation algorithm consisting of an image processing and optimization algorithm. This algorithm realizes navigation with less computation time than conventional navigation algorithms using map building and path planning processes, and can cope with an environment that changes in real-time.
Keywords: Humanoid robot navigations; Indoor environment; Monocular cameras; Navigation algorithms; Optimization algorithms; Personal service robots; Planning process; Public facilities; bipedal humanoid robot navigation; indoor environment navigation; particle swarm optimization